2022
DOI: 10.31557/apjcp.2022.23.1.241
|View full text |Cite
|
Sign up to set email alerts
|

Different Cytotoxic Effects of Vetiver Oil on Three Types of Cancer Cells, Mainly Targeting CNR2 on TNBC

Abstract: prostate, uterus, and vascular endothelium. Therefore, this receptor is dominant in cognitive function, memory, anxiety, pain, motor regulation, and endocrine regulation (Dhopeshwarkar and Mackie, 2014). Meanwhile, high expression of CNR2 is found in the immune system cells, but it is also functionally expressed in the brain (Feng et al., 2015;Elbaz et al., 2017). The different tissue distributions of CNR1 and CNR2 allow different receptor effects with selective and specific activation pathways. Both types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…On the other hand, PGV-1 targets the M phase, specifically the prometaphase (Lestari et al 2019;Meiyanto et al 2022). The different target of cell cycle inhibition could result in strong cell growth inhibition and lead to apoptosis (Suski et al 2021;Hanifa et al 2022). In this regard, we found that HST elicited modulation of apoptosis of T47D cells at 48 h. Uniquely, HST also causes cell autophagy (Lin et al 2023).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…On the other hand, PGV-1 targets the M phase, specifically the prometaphase (Lestari et al 2019;Meiyanto et al 2022). The different target of cell cycle inhibition could result in strong cell growth inhibition and lead to apoptosis (Suski et al 2021;Hanifa et al 2022). In this regard, we found that HST elicited modulation of apoptosis of T47D cells at 48 h. Uniquely, HST also causes cell autophagy (Lin et al 2023).…”
Section: Discussionmentioning
confidence: 75%
“…Once the conversion of tetrazolium salts to blue formazan crystals was complete, as denoted by their visible presence, 100 µL of 10% sodium dodecyl sulfate (SDS) stopper was introduced, and the cells were left to incubate overnight. The measurement of absorbance at 595 nm was performed using an ELISA reader (Bio-Rad) (Hanifa et al 2022).…”
Section: Mtt Assaymentioning
confidence: 99%
“…Ten percent of sodium dodecyl sulfate in 0.01 N HCl as the stopper reagent was added to dissolve the formed formazan. The absorbance was measured at 595 nm using a microplate reader (Hanifa, et al, 2022). The concentration that inhibits 50% of cell viability (IC 50 ) value of the agents was obtained and used for the combination assay (⅛, ¼, and ½ of IC 50 for COE or sinensetin and doxorubicin).…”
Section: Mtt (3-(4 5-dimethylthiazolyl-2)-2 5 Diphenyltetrazolium Bro...mentioning
confidence: 99%
“…[20] Recently, essential oil has shown great potential in antitumor activities, including TNBC. [21][22][23] Whether CEO has an inhibitory effect on TNBC arouses our interest.…”
Section: Introductionmentioning
confidence: 99%
“…The overall 5‐year survival rate of TNBC is about 77 %, and the 5‐year survival rate of advanced patients is only 14 % [20] . Recently, essential oil has shown great potential in antitumor activities, including TNBC [21–23] . Whether CEO has an inhibitory effect on TNBC arouses our interest.…”
Section: Introductionmentioning
confidence: 99%